Continued Adaptation of C4 Photosynthesis After an Initial Burst of Changes in the Andropogoneae Grasses. (7th October 2019) - Bianconi, Matheus E; Hackel, Jan; Vorontsova, Maria S; Alberti, Adriana; Arthan, Watchara; Burke, Sean V; Duvall, Melvin R; Kellogg, Elizabeth A; Lavergne, Sébastien; McKain, Michael R; Meunier, Alexandre; Osborne, Colin P; et al.
Abstract: C$_{4}$ photosynthesis is a complex trait that sustains fast growth and high productivity in tropical and subtropical conditions and evolved repeatedly in flowering plants. One of the major C$_{4}$ lineages is Andropogoneae, a group of $\sim $ 1200 grass species that includes some of the world's most important crops and species dominating tropical and some temperate grasslands. Previous efforts to understand C$_{4}$ evolution in the group have compared a few model C$_{4}$ plants to distantly related C$_{3}$ species so that changes directly responsible for the transition to C$_{4}$ could not be distinguished from those that preceded or followed it. In this study, we analyze the genomes of 66 grass species, capturing the earliest diversification within Andropogoneae as well as their C$_{3}$ relatives. Phylogenomics combined with molecular dating and analyses of protein evolution show that many changes linked to the evolution of C$_{4}$ photosynthesis in Andropogoneae happened in the Early Miocene, between 21 and 18 Ma, after the split from its C$_{3}$ sister lineage, and before the diversification of the group. This initial burst of changes was followed by an extended period of modifications to leaf anatomy and biochemistry during the diversification of Andropogoneae, so that a single C$_{4}$ origin gave birth to a diversity of C$_{4}$ phenotypes during 18 million years of speciation events and migration across geographic and ecological spaces. Our comprehensive approach and broad sampling of the diversity in the group reveals that one key transition can lead to a plethora of phenotypes following sustained adaptation of the ancestral state. [Adaptive evolution; complex traits; herbarium genomics; Jansenelleae; leaf anatomy; Poaceae; phylogenomics.]